The Influence of Deferred Tax Burden, Tax Planning, and Deferred Tax Assets on Earnings Management Strategy - Novita, Lisa; Putri, Adriyanti Agustina; Ramashar, Wira; Nursida, Nina (Research in Accounting Journal (RAJ), 2023)
This study aims to analyze and provide empirical evidence on the influence of deferred tax burden, tax planning, and deferred tax assets on earnings management. The population used in this research consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study employs purposive sampling, with a total sample of 120 data points. The data analysis tool used is multiple linear regression and classical assumption tests using the SPSS application. The results of this study indicate that the Deferred Tax Burden has no effect on Earnings Management. Meanwhile, Tax Planning and Deferred Tax Assets have an effect on Earnings Management.